2020
DOI: 10.20944/preprints202012.0346.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uptake and Correlates of Cervical and Breast Cancer Screening Among Women in Jordan: National Results of the 2017-2018 Population and Family Health Survey

Abstract: The study aimed to estimate the prevalence and associated factors of cervical and breast cancer screening among women in the general population in Jordan. Nationally representative cross-sectional data were analysed from 14,689 women (34 years median age, range 15-49) that took part in the “2017-18 Jordan Population and Family Health Survey”. Information about cancer screening uptake included Pap smear, clinical breast examination, and mammography. Results indicate that the prevalence of ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Further review was obtained of the full texts of 50 citations and 41 studies were not included owing to the reasons mentioned in the above Figure 4. Therefore, this scoping review included a total of 9 articles [26], [27], [28], [29], [30], [31], [32], [33], and [34]. All studies were published between 2003 and 2023, out of which 50% of studies were within the last five years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Further review was obtained of the full texts of 50 citations and 41 studies were not included owing to the reasons mentioned in the above Figure 4. Therefore, this scoping review included a total of 9 articles [26], [27], [28], [29], [30], [31], [32], [33], and [34]. All studies were published between 2003 and 2023, out of which 50% of studies were within the last five years.…”
Section: Resultsmentioning
confidence: 99%
“…The employment status and perception of the cost were strongly associated. The higher decision-making power and higher education levels were related with the uptake of Pap smear [27]. The higher favourable attitudes were shown by married women and illiterate towards CCS.…”
Section: Knowledge and Practice Of Cervical Cancer Screeningmentioning
confidence: 90%
See 2 more Smart Citations
“…The findings that we found related to the low rate of awareness of protective health services among Syrian refugees have similarities with the outcomes of some previous studies conducted on Arab women. For instance, a study conducted on the employment of these screening tests among women in Jordan reported that the prevalence of Pap smear cancer screening and mammogram was 15.3%, and 8.7%, respectively [ 57 ]. Moreover, a study based on attitudes toward cervical cancer screening of Muslim women immigrants living in the U.S. has also shown a lower rate of cancer screening activities among this population [ 58 ].…”
Section: Discussionmentioning
confidence: 99%